233k views
5 votes
Graph the function. g(x) = 1/3(x - 6)^2 + 1

Graph the function. g(x) = 1/3(x - 6)^2 + 1-example-1
User CreMedian
by
5.4k points

1 Answer

3 votes

ANSWER:

Explanation:

What we will do is give values to x to be able to graph the following function:


g(x)=(1)/(3)(x-6)^2+1

We give it the following values like this:


\begin{gathered} g(0)=(1)/(3)(0-6)^2+1=13\rightarrow(0,13)_{} \\ g(2)=(1)/(3)(2-6)^2+1=6.33\rightarrow(2,6.33)_{} \\ g(4)=(1)/(3)(4-6)^2+1=2.33\rightarrow(4,2.33)_{} \\ g(6)=(1)/(3)(6-6)^2+1=1\rightarrow(6,1)_{} \\ g(8)=(1)/(3)(8-6)^2+1=1\rightarrow(8,2.33)_{} \\ g(10)=(1)/(3)(10-6)^2+1=2.33\rightarrow(10,6.33)_{} \\ g(12)=(1)/(3)(12-6)^2+1=13\rightarrow(12,13)_{} \end{gathered}

Now you graph these points and we join them and we have the following:

Graph the function. g(x) = 1/3(x - 6)^2 + 1-example-1
Graph the function. g(x) = 1/3(x - 6)^2 + 1-example-2
User Madfriend
by
5.8k points